2006
DOI: 10.1002/jso.20508
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of hyperthyroidism in patients with thyroid cancer in an area of iodine deficiency

Abstract: The existence of hyperthyroidism among patients with differentiated TC is a clinical entity. Patients with hyperthyroidism and nodules require a careful approach in order to establish or exclude the possibility of TC especially in formerly iodine deficient areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…These controversies may be due to the populations studied, treatment modalities, or patient factors. In the present study, we evaluated the importance of several factors to the prognosis of DTC in 382 patients living in an iodine-deficient area [10,11]. In our study, the mean age at diagnosis was 47 years and the female to male ratio was 2.7/1.…”
Section: Discussionmentioning
confidence: 97%
“…These controversies may be due to the populations studied, treatment modalities, or patient factors. In the present study, we evaluated the importance of several factors to the prognosis of DTC in 382 patients living in an iodine-deficient area [10,11]. In our study, the mean age at diagnosis was 47 years and the female to male ratio was 2.7/1.…”
Section: Discussionmentioning
confidence: 97%
“…However, under several pathological conditions like Graves' disease, tumors of thyroid and pituitary gland stimulate thyroid cells to produce more hormones, which results in a hyperthyroid state [2]. Alterations in the level of these hormones lead not only to altered basal metabolic rate but also to many health problems.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed a 2.8% incidence of hyperthyroidism among patients with thyroid malignancy in an iodine-deficient area. [ 4 ] The reported sites of autonomous hyperfunctioning thyroid cancer are either at the primary site at the thyroid bed, which is seen as a hot nodule on thyroid scintigraphy,[ 1 5 6 7 8 9 ] or at a metastatic site. [ 10 11 12 13 14 15 ] Some reported the mechanism of activated receptors on the cancer cells with high level of TSH-binding inhibitory immunoglobulin and thyroid stimulating antibody in the absence of thyroid tissue, occurred in metastatic site after the completion of radioiodine treatment for many years.…”
Section: Discussionmentioning
confidence: 99%